Metabolomics Approach Based on Multivariate Techniques for Blood Transfusion Reactions - Lee, Seul Ji; Wang, Haiping; Ahn, Soo Hyun; Son, Mi Kwon; Hyun, Gyu Hwan; Yoon, Sang Jun; Lee, Jeongmi; Park, Jeong Hill; Lim, Johan; Hong, Soon Sun; Kwon, Sung Won (Scientific Reports, 2019)
Blood transfusions temporarily improve the physical state of the patient but exert widespread effects on immune and non-immune systems. Perioperative allogeneic blood transfusions (ABT) are associated with various risks, including coagulopathy, incompatibility, transmission of infectious agents, and allergic reactions. Nevertheless, little is known about the global metabolic alterations that reflect the possible reactions of blood transfusions. In this study, we investigated metabolite changes generated by ABT in a rat model using metabolomics technology. To further profile the “metabolome” after blood transfusions, we used both liquid chromatography-quadrupole time-of-flight high-definition mass spectrometry and gas chromatography-mass spectrometry. ABT promoted a stimulatory microenvironment associated with a relative increase in glucose transporter 1/4 (GLUT1/GLUT4) expression. Supporting this result, glucose metabolism-related enzyme IRS1 and interleukin-6 (IL-6) were abnormally expressed, and levels of lysophosphatidylcholine (LysoPC) and its related enzyme phospholipase A2 (PLA2) were significantly altered in allogeneic groups compared to those in autologous groups. Finally, amino acid metabolism was also altered following ABT. Taken together, our results show a difference between autologous and allogeneic blood transfusions and demonstrate correlations with cancer-associated metabolic changes. Our data provide endogenous information for a better understanding of blood transfusion reactions.
Keywords: Chromatography, High Pressure Liquid; Enzyme-Linked Immunosorbent Assay; Gas Chromatography-Mass Spectrometry; Humans; Metabolic Networks and Pathways; Metabolome; Metabolomics; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; Transfusion Reaction